PENGARUH LIKUIDITAS, SOLVABILITAS DAN RENTABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR INDUSTRIALS DI BURSA EFEK INDONESIA - Leni Marlina; Fransiska Enalia (Fakultas Ekonomi, 2026)
The purpose of this study is to investigate the effect of liquidity, solvency, and profitability on firm value in industrial companies listed on the Indonesia Stock Exchange. This study addresses a gap in the existing literature, as previous studies have not provided conclusive results on this topic. This study uses secondary data from industrial companies listed in Indonesia from 2020 to 2024, covering 65 companies, but the sample size was 45 companies and 215 data points. The sample size was determined using a non-probability sampling method, where samples were selected based on certain criteria. Analysis was performed using multiple linear regression with Eviews13 for data processing. The results show that Liquidity (CR) affects firm value (PBV), while Solvency (DER) and Profitability (ROA) do not significantly affect firm value (PBV).